Proceedings of the 2016 5th International Conference on Civil, Architectural and Hydraulic Engineering (ICCAHE 2016) 2016
DOI: 10.2991/iccahe-16.2016.21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis On The Method Of Highway Carbon Sink Forest

Abstract: Abstract:In view of principle greening the basic design of the road in China, introducing the advanced concept of forest carbon sequestration, combined with afforestation project of carbon measurement and monitoring guidelines, to establish the quantitative and monitoring model of highway plant carbon sink. In order to improve the highway on both sides of the green plant quality, to carry out construction of forest carbon sinks, to achieve low carbon road and is of great importance to energy conservation and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The potential for carbon sequestration and climate change mitigation of afforestation of these lands have been studied in various jurisdictions, notably, in Canada, as part of a portfolio of naturebased solutions [3][4][5]. Lands alongside road networks are examples of under-utilized areas that could contribute to increased carbon storage through afforestation [6][7][8][9][10]. These strips of land, which extend from the edge of the road to the surrounding landscape, are typically managed by government services at the city, province, or country level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for carbon sequestration and climate change mitigation of afforestation of these lands have been studied in various jurisdictions, notably, in Canada, as part of a portfolio of naturebased solutions [3][4][5]. Lands alongside road networks are examples of under-utilized areas that could contribute to increased carbon storage through afforestation [6][7][8][9][10]. These strips of land, which extend from the edge of the road to the surrounding landscape, are typically managed by government services at the city, province, or country level.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the success of active management programs dedicated to roadsides. For instance, a tree planting initiative along highway borders in China sequestered 4.68 Mg C between the 1980s and 2005 [9]. Similarly, in the United States of America, Ament and Begley [11] found that tree plantation along 485,255 km of roads had the potential to sequester 8 Mg C per year.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that properly managed urban plantations near highways can sequester more carbon than natural forests (Hutrya et al, 2011;Tang et al, 2016). In China, a tree planting project along highway borders absorbed 4.68 million tonnes of carbon between the 1980s and 2005 (Cheng et al, 2016). In the United States, trees along 485,255 km of roads were estimated to sequester 8 million tonnes of carbon annually (Ament & Bengley, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nonlinear damage identification method based on time series models tends to use nonlinear time series models. Cheng et al 11 proposed a nonlinear damage identification method based on ARMA/GARCH (generalized autoregressive conditional heteroskedasticity) model. An ARMA/GARCH model for the story acceleration time series was established, and the time series data were divided into the baseline state and the test state.…”
Section: Introductionmentioning
confidence: 99%